Estimated glomerular filtration rate but not solute carrier polymorphisms influences anemia in HIV–hepatitis C virus coinfected patients treated with boceprevir or telaprevir-based therapy. (24th August 2016) - Kheloufi, Farid; Bellissant, Eric; Cotte, Laurent; Poizot-Martin, Isabelle; Quaranta, Sylvie; Garraffo, Rodolphe; Barrail-Tran, Aurélie; Renault, Alain; Fournier, Isabelle; Lacarelle, Bruno; Bourlière, Marc; Molina, Jean-Michel; et al.
Abstract : Objectives: Ribavirin (RBV) induced anemia may be influenced by host genetic factors affecting RBV transport solute carrier (SLC) or metabolism inosine triphosphatase (ITPA), as already reported. We investigated the influence of single nucleotide polymorphisms (SNPs) on SLC genes on anemia, RBV trough concentration (Ctrough ) and response in HIV–hepatitis C virus coinfected patients receiving triple therapy with boceprevir or telaprevir. Methods: Patients from the ANRS HC26/HC27 studies were genotyped for SLC28A3 SNPs (rs10868138 and rs56350726) and SL29A1 SNPs (rs760370). Hemoglobin (Hb) decline was collected at baseline day 0 (D0), week 4 (W4) and week 8 (W8), and RBV Ctrough was measured at W4 and W8 by HPLC. A multivariate analysis including SLC SNPs, estimated glomerular filtration rate (eGFR), ITPA deficiency and RBV Ctrough was performed to determine predictive factors of anemia and response. Results: SLC genotyping was performed in 130 patients. Neither SLC28A3 nor SLC29A1 SNPs were associated with Hb decline both at W4 and W8. No association was found between SLC polymorphisms and RBV Ctrough . Independent predictive factors of Hb decline at W4 were D0 Hb, ITPA deficiency and W4 RBV Ctrough in the multivariate analysis ( P < 0.05). Only D0 Hb, W4 RBV Ctrough and eGFRD0–W8 were predictive of anemia at W8 ( P < 0.05). Response was not influenced by SLC SNPs. Conclusion: eGFR, but not SLC polymorphisms, influences anemia in HIV–hepatitis C virus coinfected patients receiving boceprevir-based or telaprevir-based therapy. RBV is still a cornerstone of hepatitis C treatment, thus renal function and RBV Ctrough should be monitored in patients receiving RBV regimen combined with first-generation direct-acting antiviral agent.